E-Commerce Liability to Consumers For the Sale of Black Market Products - Rizqi, Aditya Maulana; Ramli, Muhammad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The rapid expansion of e-commerce has significantly transformed consumer purchasing behaviors, but it has also given rise to the sale of black market goods through online platforms, raising critical concerns about consumer protection and regulatory oversight. This study investigates the responsibilities of e-commerce platforms regarding the sale of black market products and evaluates the effectiveness of legal and regulatory frameworks currently in place. Adopting a normative juridical research method, this study involves a thorough analysis of existing laws, regulations, and industry standards pertaining to e-commerce and black market transactions. By examining legal texts, regulatory guidelines, and case law, this research identifies gaps in the current legal framework and assesses its adequacy in addressing black market activities. The results indicate that while legal provisions exist, they are often insufficiently enforced and lack clarity in their application to emerging e-commerce practices. The study concludes that e-commerce platforms must advocate for stronger legal reforms and clearer regulations to enhance consumer protection. Additionally, improved transparency in platform policies and heightened regulatory scrutiny are necessary to better address the challenges posed by black market goods. Future research should explore the development of more comprehensive legal strategies and frameworks to effectively combat black market transactions in the digital realm.